IMPLEMENTASI PERATURAN DAERAH NOMOR 21 TAHUN 2010 TENTANG PAJAK RESTORAN TERHADAP PENINGKATAN PAJAK PADA DINAS PENDAPATAN DAERAH KABUPATEN SIDENRENG RAPPANG - Herman D Herman D; Ani Ardian (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The objective of the research were to find out the implementation of the Regional Regulation Number 21/2010 year about Tax to Increase Local Tax Restaurants Service SidenrengRappang. The population of the research are all across the taxpayer in SidenrengRappang as many as 44 taxpayers.the sample in this research were taken by using total sample or samples saturated. The data of this research were collected by using observation, questionnaires, interviews, and library research (documentation). The data obtained were processed using with the help of frequency tables and percentages. The result of data analysis showed that there (1) implementation of the Regional Regulation Number 21/2010 Year on the Local Tax Increase Tax Revenue Service SidenrengRappang considered influential had value of 74% but there is one less running maximum indicator that is consistent with a value of 38,6%. (2) Factors that affect the implementation of the Regional Regulation No. 21/2010 Year on the Local Tax Increase Tax Revenue Service SidenrengRappang ie amounting to Resources by 60% , 72,8% Communication, Structures bureaucracy by 79 and 97,2% Dispositions.